COSMOGENIC CHLORINE-36 FROM CALCIUM SPALLATION - Stone J.O.; Allan G.L.; Fifield L.K.; Cresswell R.G. (My University, 1996)
Calcium is a major target element for cosmogenic 36Cl production. Consequently 36Cl rapidly reaches detectable levels in minerals such as calcite and calcium feldspar exposed at the Earth's surface. Spallation of calcium isotopes typically accounts for 80-90% of 36Cl production in these minerals, with subsidiary contributions from negative muon capture by 40Ca and thermal neutron capture by 35Cl. To provide a basis for surface exposure dating, we have calibrated cosmogenic 36Cl production in calcium feldspar from the 17,300 year old Tabernacle Hill basalt. At an altitude of 1445 m and an effective geomagnetic latitude of 40.9° the calcium spallation rate is 152 +/- 11 atoms (g Ca)-1 a-1. The corresponding rate at sea level and high latitude is estimated at 48.8 +/- 3.4 atoms (g Ca)-1 a-1. The muon capture rate used to derive these values is 8.8 +/- 2.2 atoms (g Ca)-1 a-1 at the Tabernacle Hill site, scaled from a value of 4.8 +/- 1.2 atoms (g Ca)-1 a-1 at sea level and high latitude. The calcium spallation rate determined in this study is in excellent agreement with previous whole-rock calibration measurements at Tabernacle Hill, when these are recalculated with respect to the absolute timescale.The calibration of 36Cl production from calcium underpins development of an exposure dating technique for calcite. Due to its high calcium content, the 36Cl production rate in calcite is higher than in any other common rock-forming mineral. Measurement of 36Cl in calcite, with an accelerator mass spectrometric detection limit of #5 x 103 atoms per gram, allows dating of limestone surfaces exposed for periods ranging from #102-106 years. Alternatively, erosion rates from less than 1 to greater than 1000 μm per year can be determined in the case of eroding karst surfaces. Though the 36Cl production rate is lower in calcium feldspar than in calcite, measurements on this mineral will provide a useful means of dating young basalt lavas.